Oseltamivir phosphate for suspension is bioequivalent to TAMIFLU in healthy volunteers: a randomized, open-label clinical study - Ying Wang; Bangzhong Tang; Jing Xie; Xiaoqin Wang; Peng Ren; Guangmei Wu; Cuixia He; Minhui Zhu; Yue Su; Jiaxiang Ding; Yuanyuan Xu; Ling Fan; et al. (BMC, 2023)
Abstract Purpose The study was aimed at evaluating the bioequivalence and safety of oseltamivir phosphate for suspension, provided by Shenzhen Beimei Pharmaceutical Co. Ltd. and manufactured by Hetero Labs Limited, and the reference product TAMIFLU® in healthy Chinese subjects. Methods A single-dose, randomized, two-phase, self-crossed model was adopted. Among 80 healthy subjects, 40 subjects in the fasting group and 40 subjects in the fed group. Subjects in the fasting group were randomized into two sequences according to the proportion of 1:1, each given 75 mg/12.5 mL of Oseltamivir Phosphate for Suspension or TAMIFLU®, and cross-administered after 7 days. Postprandial group is the same as fasting group. Results The Tmax of TAMIFLU® and Oseltamivir Phosphate for Suspension in the fasting group were 1.50 h and 1.25 h, which in the fed group were both 1.25 h. Geometrically adjusted mean ratios of the PK parameters of Oseltamivir Phosphate for Suspension along with TAMIFLU® under fasting and postprandial conditions were in the range of 80.00-125.00% at the 90% confidence interval (CI). The 90% CI of Cmax, AUC0-t, AUC0-∞ for fasting group and postprandial group were (92.39,106.50), (94.26,100.67), (94.32,100.89) and (93.61,105.83),(95.64,100.19),(96.06,102.66). Among the subjects on medication, a total of 18 subjects reported 27 adverse events, all of which were treatment-emergent adverse events (TEAEs), six of these TEAEs were rated as grade 2 in severity and the rest were as grade 1. The number of TEAEs in the test product and the reference product were 14,13 respectively. Conclusion Two Oseltamivir phosphate for suspensions are safe and bioequivalent.